2005
DOI: 10.1038/nature03440
|View full text |Cite
|
Sign up to set email alerts
|

The DNA sequence of the human X chromosome

Abstract: The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
1,045
5
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,006 publications
(1,105 citation statements)
references
References 68 publications
32
1,045
5
13
Order By: Relevance
“…The mammalian X chromosome contains more than 1,000 genes and many are house-keeping genes (Ross et al 2005). X chromosome inactivation (XCI) is a biological process utilized by mammals to ensure equal expression of X-linked genes between males and females (Lyon 1961).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian X chromosome contains more than 1,000 genes and many are house-keeping genes (Ross et al 2005). X chromosome inactivation (XCI) is a biological process utilized by mammals to ensure equal expression of X-linked genes between males and females (Lyon 1961).…”
Section: Introductionmentioning
confidence: 99%
“…The present-day human X and Y chromosomes retain only traces of their shared ancestry as identical autosomes. The euchromatic portion of the male-specific region of the Y chromosome (MSY) is roughly 1/6th the size of the X chromosome and has onlỹ 1/12th of the number of genes Ross et al 2005). In other words, there is little doubt that, in essence, the Y chromosome is a degraded X (Ohno's hypothesis).…”
Section: Introductionmentioning
confidence: 99%
“…Fundamentally, the argument is that the Y chromosome has been degenerating for millions of years and it is only a matter of time before it disappears completely. Jenny explained that the human X is a decent-sized chromosome bearing~1,000 proteincoding genes (Ross et al 2005), over-endowed in "brains-and-balls" genes involved in reproduction and intelligence (often both). The tiny Y is a genetic wasteland, full of "junk" and bearing only 45 genes that code for different proteins, most of which are active only in the testis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them 83 genes are located on X chromosome (3). It is reported that, about 10% of the genes on the X chromosome are CT antigen genes (4), and these CT-X genes are notably more testis-restrictively than those on other chromosomes (5). However, CT proteins expression shows heterogeneous in many cancers including lung carcinoma, therefore more CT antigens need to be identified to develop the polyvalent vaccines to avoid immune escape of tumors (1,6).…”
Section: Introductionmentioning
confidence: 99%